Insurance coverage among women diagnosed with a gynecologic malignancy before and after implementation of the Affordable Care Act - Moss, Haley A.; Havrilesky, Laura J.; Chino, Junzo (Gynecologic oncology, 2017)
The Patient Protection and Affordable Care Act (ACA) included provisions to expand insurance coverage by expanding Medicaid eligibility, providing subsidies of private coverage and enforcing an individual mandate. The objective of this study is to examine the impact of the ACA on insurance rates among women diagnosed with a gynecologic malignancy. Using Surveillance, Epidemiology, and End Results 18 registries database, women newly diagnosed with cervical, uterine or ovarian cancer between 2008 and 2014 were identified. Insurance rates were examined before and after the passage of the ACA (2011) as well as before (January 2011–December 2013) versus after (January 2014–December 2014) Medicaid expansion to examine the impact of specific provisions. Rates of insurance were then compared between states that elected for expansion of Medicaid in 2014 vs. those states that had not. Among 181,866 diagnosed with cervical, uterine or ovarian cancer, there was a significant increase in patients enrolled in Medicaid after 2011. Between 2011 and 2014, there was a significant decrease in the rates of uninsured for all cancer types (p=0.001). Uninsured rates decreased by 50% for those diagnosed with uterine and ovarian cancer (6% to 3% and 8% to 4% respectively, p≤0.001), and by 25% in cervical cancer (8.9% to 6.7%, p=0.001) after January 2014. Decreases in the rate of the uninsured and associated increases in insurance coverage were only observed in states which expanded Medicaid coverage (p≤0.001). The Affordable Care Act resulted in expanded insurance coverage for women diagnosed with a gynecologic cancer, however, the impact was significantly increased in states which increased their Medicaid eligibility in 2014. •The Affordable Care Act (ACA) includes provisions to expand insurance coverage.•Insurance coverage for women diagnosed with a gynecologic cancer has increased.•Rates of uninsured unchanged in states that did not increase Medicaid eligibility.